Titer disparity of anti-Spike receptor binding domain SARS-CoV-2 antibody between vaccinated and naturally infected individuals - Dewa P. Surawan; Duwi Sumohadi; Anak AG. Budhitresna; Putri P. Lestari; Kartika Dewi; Wasudewa Wikananda; Retenra P. Suwari; Md. Rabiul Islam; Haypheng Te; Ali A. Rabaan; Sri Masyeni (Narra Sains Indonesia, 2022)
In conjunction with other health promotion strategies, vaccination of coronavirus disease 2019 (COVID-19) is a strategy to alleviate the burden of infection. The aim of this study was to determine the differences in antibody response strength between individuals who received COVID-19 vaccination and those who had a natural infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A cross-sectional study was conducted among post-natural confirmed COVID-19 infection and immunized people in Bali, Indonesia. The vaccination was using Sinovac-CoronaVac with two-weeks interval between the two vaccine doses. To measure the level of anti-Spike receptor binding domain (SRBD) of SARS-CoV-2 antibody, we used Roche electro-chemiluminescence immunoassay (ECLIA) platform. Blood samples were obtained before and 28 days after first immunization in the vaccinated group, as well as two weeks after hospital discharge in the confirmed COVID-19 patients based on real-time reverse transcription polymerase chain reaction (RT-PCR). A total of 58 confirmed COVID-19 patients and 60 vaccinated individuals were included. On the 28th day after the initial vaccination, the seroconversion rate among vaccinated individuals was 91.67%. The mean titer of anti-SRBD SARS-CoV-2 antibody among vaccinated participants was 63.62±82.57 IU/mL (ranged between 0 IU/mL and 250 IU/mL). The mean titer among naturally infected group was 188.47±94.57 IU/mL (ranged between 4.25 IU/mL to 250 IU/mL) regardless the severity of COVID-19. Our data suggested that the titer of anti-SRBD SARS-CoV-2 antibody was significantly higher in naturally infected individuals compared to those who received COVID-19 vaccination (p<0.001). These data suggest that not all individuals vaccinated with Sinovac COVID-19 had protective level of anti-SRBD SARS-CoV-2 antibody and booster dose of heterologous vaccine maybe required.